2015
DOI: 10.1097/sle.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Endoscopic Mucosal Resection for Management of Small Duodenal Neuroendocrine Tumors

Abstract: EMR for small duodenal NETs can be a safe and effective alternative to surgery in carefully selected patients. EUS is a useful adjunct in determining depth of invasion for duodenal NETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Die in über 90 % weniger als 2 cm messenden und funktionell nicht in Erscheinung tretenden Tumoren zeigen immunhistochemisch meist eine Expression für Somatostatin, bei erhöhter Ki-67-Rate dagegen vermehrt eine Calcitonin-Expression. In beiden Fällen ist bei kleinem Primärtumor und Fehlen hormoneller Symptome die endoskopische Entfernung der rein submukösen Tumore ausreichend [303,304].…”
Section: Pankreas-netunclassified
“…Die in über 90 % weniger als 2 cm messenden und funktionell nicht in Erscheinung tretenden Tumoren zeigen immunhistochemisch meist eine Expression für Somatostatin, bei erhöhter Ki-67-Rate dagegen vermehrt eine Calcitonin-Expression. In beiden Fällen ist bei kleinem Primärtumor und Fehlen hormoneller Symptome die endoskopische Entfernung der rein submukösen Tumore ausreichend [303,304].…”
Section: Pankreas-netunclassified
“…EMR technique was successful and safe treatment options for most small D‐NETs [7]. This safety issue was confirmed by more and more recent case series reported in the literatures [8,9]. Moreover, the EUS plays an important and unique role in the case of D‐NETs in evaluating the depth of invasion of the duodenal wall and in assistance for initial treatment strategy made.…”
Section: Discussionmentioning
confidence: 87%
“…[4] Another study reported that duodenal carcinoid tumors are indolent when they are small (<10–20 mm) and localized in the submucosa. [7,11] The malignancy features of duodenal carcinoid tumors embedded in the submucosa are angioinvasion, high mitotic figures, and larger lesion size. [4] In the present study, we performed EMR for duodenal carcinoid tumors without malignant features.…”
Section: Discussionmentioning
confidence: 99%